PEMERIAN KECAKAPAN REPRESENTASI MATEMATIS SISWA SMP DALAM MATERI BANGUN RUANG SISI DATAR - Kirana Qurotal Aini Prawira; Jarnawi Afgani Dahlan; Tia Purniati (Tatar Pasundan: Jurnal Diklat Keagamaan, 2023)
This research was carried out to expose the potential for mathematical representation of geometric materials. Students in the middle grades were used for this study. Case study methodology is used to conduct this study from a qualitative perspective. A mathematical representation instrument based on a five-item description is utilised to convey the findings of the inquiry. According to the findings, out of the four indications of "mathematical representation," students' abilities on picture representation indicators are higher than their abilities on other indicators of "mathematical representation," such as visual, mathematical expressions, and text representation. According to the other findings, the capability of representing text had the lowest ability overall, as shown by the number of students who were unable to solve the problem that was presented to them. Other results showed that text representation had the lowest ability, as seen by the number of students who did not complete the assignment.Keywords: mathematical representation skill; planar shape; problem-solving aptitude